KANT CRISIS - Carter, William H (Imaginations: Journal of Cross-Cultural Image Studies, 2011)
• ISSUE 2-1, 2011 • 68 KANT CRISIS This study approaches the last days of Immanuel Kant through the lens of his contemporary biographers and other correspondents. Among the latter, Kant’s brother and, subsequently, his brother’s family provide a symptomatic reflection upon Kant’s management of his genealogy and his legacy. Yet behind this body of work is another corpus, one which embodies maternal and paternal legacies that are not readily subsumed by Oedipus or Kant’s philosophy. This work (of art) is Kant’s own body or corpus, which he painstakingly maintained and which provided a case study for his refelctions on preventive medicine in The Conflict of the Faculties. William H. Carter studied at the University of Virginia, the University of Heidelberg, and earned his Ph.D. at the University of California, Santa Barbara. He taught German for three years at Tulane University and recently returned to the Department of World Languages and Cultures at Iowa State University, where he began his teaching career. His current book project is titled “Devilish Details: Goethe’s Public Service and Political Economy.” Julian Fickler attends the Academy of Fine Arts Karlsruhe, class of Helmut Dorner. He is the recipient of a prestigious fellowship award bestowed by the Künstlerförderung des Cusanuswerks Bonn. He has exhibited solo locally and in group at venues in Berlin and Hamburg.